The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1108/ijtc-03-2021-0040
|View full text |Cite
|
Sign up to set email alerts
|

Halal destination attributes and revisits intention: the role of destination attractiveness and perceived value

Abstract: Purpose The growing numbers of Muslims visiting halal destinations motivated this study to explore halal destination attributes and revisit intention. This study aims to investigate how halal destination attributes affect destination attractiveness. Hence, it identifies the influence of halal destination attributes on perceived value, including functional and emotional value. It also verifies the effect of destination attractiveness on both functional value and emotional value. Finally, this framework verifies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 40 publications
1
19
0
Order By: Relevance
“…The study has uniquely contributed to the enhancement of halal tourism in Bangladesh by verifying the direct effects of halal friendly attributes (e.g. halal social environments, halal food and beverages, halal services, halal entertainments, halal staff clothing and emotional attachments) on halal tourism destinations revisit intentions, where halal social environments is significantly related to halal tourism destinations revisit intentions consistent with Mursid and Anoraga (2022). Aligned with the study results of Mursid (2022), the present study has confirmed that halal food and beverages significantly impact on halal tourism destinations revisit intentions.…”
Section: Discussionmentioning
confidence: 67%
“…The study has uniquely contributed to the enhancement of halal tourism in Bangladesh by verifying the direct effects of halal friendly attributes (e.g. halal social environments, halal food and beverages, halal services, halal entertainments, halal staff clothing and emotional attachments) on halal tourism destinations revisit intentions, where halal social environments is significantly related to halal tourism destinations revisit intentions consistent with Mursid and Anoraga (2022). Aligned with the study results of Mursid (2022), the present study has confirmed that halal food and beverages significantly impact on halal tourism destinations revisit intentions.…”
Section: Discussionmentioning
confidence: 67%
“…Revisiting intention denotes the likelihood that tourists are willing to revisit the same destination (Luo et al, 2021).Tourists with the intention of revisiting are essential to the destination because if they revisit the destination, these returning visitors will have lower marketing costs than those who visited for the first time, and will further bring in more consumption. As tourism becoming a vital source of revenue, many researchers and practitioners have investigated the factors that lead tourists' intention to revisit destinations (Yu et al, 2019), such as destination image (Mursid and Anoraga, 2022), tourism experience (Habibi and Rasoolimanesh, 2020), and satisfaction (Cakici et al, 2019). When tourists are highly satisfied with everything they feel during the travel process, then they have a high possibility of revisiting the destination; else, they will not have the intention to revisit (Zhang et al, 2014).…”
Section: Revisiting Intentionmentioning
confidence: 99%
“…Poria et al (2004) emphasized that the image of a heritage destination is crucial, as the "heritage image" of a particular destination is created by tourists' perception of the attributes of the destination. In travel and tourism, destination image can be viewed as the sum of beliefs, expectations, and impressions accumulated owing to evaluations of attributes at a destination (Crompton, 1979), and tourists' evaluation of destination attributes affect tourists' future behavioral intentions (Mursid and Anoraga, 2022;Piramanayagam et al, 2021). With the enhancement in the destination image, tourists' future behavioral intentions will become more positive.…”
Section: Destination Image and Revisiting Intentionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, when consumers felt that the actual price set for the product (that they want to purchase) was higher than what consumers are expecting, then discrepancy or difference between the actual price of the product and the level of price that consumers were expecting will happen, thus lowering or weakening their intention to purchase the product, and vice versa. Therefore, it is important for companies or corporations to be able to fully and meticulously understand the level of expectations that target consumers had concerning the level of price that consumers are willing to pay, in which companies' understanding regarding this concern could help or assist companies in formulating or setting the right price for all of the products or services which will be marketed or sold to the consumers which could fully satisfy consumers' expectations concerning the price that consumers had to pay for buying the product (Arora et al, 2022;Indounas, 2022;Mursid and Anoraga, 2022).…”
Section: Perceived Pricementioning
confidence: 99%